PEMBERDAYAAN KADER POSYANDU DALAM PENINGKATAN PENGETAHUAN TENTANG MANAJEMEN LAKTASI DAN ASI EKSLUSIF DI DESA BABABULO KECEMATAN PAMBOANG - Ika Muzdalia; Weny Anggraini Adhisty (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Increasing the capacity of Posyandu Cadres is needed in order to meet the target of 80% exclusive breastfeeding nationally. Exclusive breastfeeding is expected to be able to reduce the number of stunting which continues to increase in West Sulawesi Province, especially in Bababulo Village, Pamboang District. The role of Posyandu cadres in increasing the understanding of pregnant women and breastfeeding mothers about fulfilling exclusive breastfeeding and optimizing the government's program, namely exclusive breastfeeding. The purpose of this training activity is to increase knowledge and empower posyandu cadres in Exclusive Lactation and Breastfeeding Management. The method used in the activity is pretest, training, counseling and post test. This community service activity was carried out with partners from the Babaulo Village Health Center, Pamboang District. The activity participants were all Posyandu cadres in Bababulo Village, namely 25 people. The implementation of this activity was carried out for 3 days from 21-23 July 2023. The results of this activity showed that there was an increase in the knowledge of posyandu cadres after training and counseling on Lactation Management and Exclusive Breastfeeding. Seeing these results, it was concluded that posyandu cadre empowerment activities could increase knowledge about lactation management and exclusive breastfeeding in Bababulo Village, Pamboang District.